Modelo predictivo para identificar factores que influyen en la rotación del personal en una organización del sector business process outsourcing (bpo) en medellín. (2019)
This document presents a predictive model that identifies the main factors that influence staff turnover, for example demographic factors like age, gender and marital situation; socioeconomic factors like salary and company aged. Each of the variables was analyzed determining their importance on the decision to withdraw from the company. This work was development in a company of the Business Process Outsorcing-BPO- At Medellín- sector, where job satisfaction surveys were realized, in addition, some data provided by production área where it were analyzed to understand the process. Four statistical models were chosen to make the variable´s choice with the greatest influence on staff turnover then, under a survival model, where people with the highest probability of rotation were identified. At the end, the main conclusions on the statistical insights are presented and some recommendations are provided for future studies.